Impact of Baseline Expectancy on Outcome Prediction of Real and Sham Acupuncture for Persistent Chemotherapy-Induced Peripheral Neuropathy Pain in Solid Tumor Survivors: A Secondary Analysis of a Randomized Clinical Trial - Xiaotong Li PhD; Lilly Zhi HSD; Katherine Y. Han BA; Susan Q. Li MS; Khalada Ahmad MD; Christina Seluzicki MBE; Rui Wang MD, PhD; Ting Bao MD, DABMA, MS (Integrative Cancer Therapies, 2023)
Background: Chemotherapy-induced peripheral neuropathy (CIPN) pain significantly worsens cancer survivors’ quality of life. Expectancy may play an important role in acupuncture response. We sought to explore whether expectancy predicts pain outcome in real acupuncture (RA) and sham acupuncture (SA) in cancer survivors. Methods: We analyzed data from a randomized clinical trial that evaluated the effect of RA on CIPN symptoms compared to SA and wait list control (WLC) in 75 cancer survivors. This secondary analysis was limited to CIPN pain measured by the Numeric Rating Scale (NRS), graded from 0 to 10. Interventions were delivered over 8 weeks. SA was implemented using a combination of non-acupuncture points and a non-insertion procedure. Patient expectancy was measured by the Acupuncture Expectancy Scale (AES) 3 times during the study. We used a linear regression model to evaluate if the NRS score was associated with the baseline AES score at the end of treatment (week 8), adjusting for baseline NRS score. Results: AES was similar among 3 groups at baseline (RA: 11.8 ± 2.7; SA: 12.1 ± 3.8.; WLC: 14.6 ± 4.2; P  = .062). Baseline AES was not found to be significantly associated with the week 8 NRS score among patients in all RA, SA, and WLC groups (all P  > .05). However, we found a trend that higher baseline AES predicted lower NRS score at week 8 in the SA group: a one-point higher score on baseline expectancy was associated with a 0.3-point reduction in NRS pain score ( P  = .059) at week 8. Conclusions: The association of baseline expectancy and acupuncture response was similar between RA and SA. However, SA seemed to rely more on expectancy than RA. Further studies with larger sample sizes are needed to confirm this finding.